THE USE OF AI APPLICATION FOR WRITING CV: DESCRIPTIVE ANALYSIS - Nernere, Maria Setyaningsih (Jurnal Smart, 2024)
Several research studies have proven how an Artificial Intelligence (AI) application eases people's jobs in writing. In this regard, AI applications and how students use them in writing Curriculum Vitae (CV) were described. Eighty business students participated in answering the online questionnaire. The result shows that instead of using AI-based-CV Maker instantly, the participants prefer AI assistance for technical skills such as translation, design and grammar checking. AI tools are only one of the tools to use due to trust issues on content and contextual background.